HAVING FUN IN THE KITCHEN: A PROJECT BASED ON THE STEAM APPROACH WITH 9TH GRADE ELEMENTARY SCHOOL STUDENTS - Minuzzo Massoni, Adriano (2022)
STEAM refers to the development of educational experiences in which the areas of science, technology, engineering, arts and mathematics are worked through interdisciplinary practices and projects. It should be noted here that this study was carried out during the pandemic period and aims to present the experience of 03 teachers in the elaboration and application of a project based on the STEAM approach for students of the 9th year of Elementary School of the Municipal Education System of Tangará da Serra -MT. The research was qualitative, applied in nature, and descriptive in terms of objectives, as a procedure, field research was carried out, outlining the realization of three face-to-face meetings with collaborating teachers, with the objective of collectively building STEAM projects in their school. The results indicated that the practical experience of the concepts of the STEAM approach was provided, such as interdisciplinary work and meaningful learning and the application of active methodologies to teachers.